THE DICHOTOMY OF IMPROVING STATE BUDGET EXPENDITURE: FROM ENSURING OPPOSITION TO RUSSIAN AGGRESSION AGAINST UKRAINE TO BUILDING A MODERN STATE INTEGRATED INTO WESTERN CIVILIZATION (World of finance, 2023)
Introduction. The period of resistance to the aggression of the Russian Federation against Ukraine implies the need to solve fundamentally new tasks facing the state and the accumulation of a large layer of previously accumulated problems. This determines the key need to improve state budget expenditures.The purpose of the article is to develop main vectors for improving the management of state budget expenditures, aimed at ensuring the ability to resist the aggression of the Russian Federation against Ukraine and the implementation of measures to build a modern state integrated into the European and Euro-Atlantic space.Results. The main vectors of improving state budget expenditures should cover a complex of directions: strengthening the organizational capacity of entities managing budget expenditures, improving priorities for the use of budget funds, establishing effective communications with society, modernizing the procedures for forming and implementing budget expenditures (budgeting technologies), and developing institutional support for the use budget funds. A set of measures has been defined for the period of resistance to the aggression of the Russian Federation against Ukraine and the period of postwar development of the country with the aim of strengthening the organizational capacity of entities managing budget expenditures, which includes the development of human capital, the introduction of the latest digital technologies, the introduction of artificial intelligence and the strengthening of partnership ties. For the specified period, directions for strengthening the priorities of budget expenditures are outlined, which involve changes in each of the functions of budget expenditures in the economic system (placement, redistribution and stimulation) and in public administration (programming and control). The introduction and application of modern budgeting technologies in Ukraine is expedient in view of the possibility of applying relevant NATO documents during the period of resistance to Russian aggression on optimizing the allocation of resources to maximize the result in the defense sphere and taking into account the potential of European and Euro-Atlantic integration in the post-war period. Identified directions in improving the formation and implementation of budget expenditures, as well as the changing external environment, necessitate the development of institutional support for the budget process.Conclusions. The well-founded composition and content of measures to improve expenditures in the conditions of resistance to the aggression of the Russian Federation against Ukraine is aimed not only at solving the tasks that are relevant for this period, but also should create a favorable environment for a flexible transition for the further modernization of relations in the field of budget expenditures in the period of the country's post-war development and successful European and Euro-Atlantic integration.